Role of Telemedicine and Impact of Covid 19 Pandemic on Diabetic Patients Management and Clinical Outcomes - Alruwaitea, Abdulmajeed; Alalwan, Abdulaziz; Alluhaymid, Yousef; Alrayes, Faisal; Aljohani, Abdulaziz (Archives of Clinical and Biomedical Research, 2023)
Background: Telemedicine has emerged as a valuable tool in managing chronic diseases like diabetes, especially during the COVID-19 pandemic. This study aims to evaluate the impact of telemedicine on diabetes management by assessing patient outcomes and healthcare accessibility. Methods: A retrospective cohort study was undertaken at King Saud University Medical City (KSUMC) located in Riyadh, Saudi Arabia. Diabetic patient visits in Family Medicine clinics were documented and implemented in an Excel sheet by the quality team at the Family Medicine department. The study period extended from January to April 2023. Patients were divided into two groups based on their albumin/creatinine ratio (ACR). And the data included demographic information, HbA1c measurements, co-morbidities, documented telemedicine interactions, and other relevant variables before and after the Covid-19 lockdown. The data collection period spanned from January 2020 to December 2020. Results: The sample comprised 121 diabetic patients, with 57% females and 43% males. The mean age was 60.68 years, and the majority (50.4%) were aged 61 years or older. During the pandemic, 81.8% of patients received telemedicine care. There were no significant differences in mean HbA1c, ACR, or BMI between the periods before and after the pandemic lockdown. Conclusion: Telemedicine played a crucial role in managing diabetic patients during the COVID-19 pandemic. While telemedicine did not directly impact ACR, patients with high ACR demonstrated poorer glycemic control. These findings highlight the need for further research and improvement in optimizing telemedicine for diabetes management, with a focus on enhancing glycemic control and patient outcomes.